Gene expression of insulin receptor, insulin-like growth factor increases and insulin-like growth factor-binding protein-3 reduces with increase in prostate size in benign prostatic hyperplasia. (3rd April 2018) - Sreenivasulu, Karli; Nandeesha, Hanumanthappa; Dorairajan, Lalgudi Narayanan; Rajappa, Medha; Vinayagam, Vickneshwaran; Cherupanakkal, Cleetus
Abstract: Introduction: Although the role of insulin in the development of benign prostatic hyperplasia (BPH) is well established, there are no studies regarding alteration in the gene expression of components of insulin-signaling pathway and their association with prostate size in BPH. Hence, the study was designed to analyze the gene and protein expression of insulin receptor and its related components in patients with BPH. Materials and methods: Twenty-seven BPH patients aged between 55 and 75 years were recruited in the study and prostatic tissues were obtained after transurethral resection of the prostate. Gene expression levels of Insulin receptor (IR), insulin receptor substrate (IRS), insulin-like growth factor (IGF) and insulin-like growth factor-binding protein-3 (IGFBP-3) were assessed by q-PCR. Results: Insulin receptor (IR-A and B) and insulin-like growth factors (IGF-1 and IGF-2) gene expression were significantly increased and IGFBP-3 gene expression was reduced in BPH patients with larger prostate size. Also, serum insulin was significantly increased and IGFBP-3 was significantly reduced in patients with larger prostate size. Conclusion: Increased expression of IR-A, B and IGF-1, 2 genes and reduced IGFBP-3 gene expression was associated with larger prostate size in BPH.